Philosophy for Children as a Method of Working with Talented Pupils or an Opportunity for Promoting Their Potential Talent - Vačun, Maja (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
Elementary school lesson is often limited by the learning objectives or knowledge standards that teachers review and assess. Students are only required to remember, and most often, in addition to knowing the 'what', they are not given the opportunity to develop other levels of thinking. The learning process should include methods and content that require abstract thinking and creativity, as well as reading complex texts. In this article we address the question of who are the "gifted" learners and the concept of working with them. We have reviewed some elementary school curricula to present the basic findings about incorporating problem-based learning. We offer philosophy for children as a way to develop students' potential and/or already identified talents. We conclude that the working methodology used in Philosophy for Children is appropriate for most subjects in elementary school and can have a positive impact on the learning and social performance of students.